TP53 /KRAS Co-Mutations Create Divergent Prognosis Signatures in Intrahepatic Cholangiocarcinoma - Guo, Chunguang; Liu, Zaoqu; Yu, Yin; Chen, Yunfang; Liu, Hui; Guo, Yaming; Peng, Zhenyu; Cai, Gaopo; Hua, Zhaohui; Han, Xinwei; Li, Zhen (Frontiers in Genetics, 2022)
Background: Due to high invasiveness and heterogeneity, the morbidity and mortality of intrahepatic cholangiocarcinoma (ICC) remain unsatisfied. Recently, the exploration of genomic variants has decoded the underlying mechanisms of initiation and progression for multiple tumors, while has not been fully investigated in ICC. Methods: We comprehensively analyzed 899 clinical and somatic mutation data of ICC patients from three large-scale cohorts. Based on the mutation landscape, we identified the common high-frequently mutation genes (FMGs). Subsequently, the clinical features, prognosis, tumor mutation burden (TMB), and pharmacological landscape from patients with different mutation carriers were further analyzed. Results: We found TP53 and KRAS were the common FMGs in the three cohorts. Kaplan-Meier survival curves, univariate and multivariate analysis displayed that TP53 and KRAS mutations were associated with poor prognosis. Considering the co-mutation phenomenon of TP53 and KRAS, we stratified patients into ‘Double-WT’, ‘Single-Hit’ and ‘Double-Hit’ phenotypes by the mutation status. Patients with the three phenotypes showed significant differences in mutation landscape. Additionally, compared with ‘Double-WT’ and ‘Single-Hit’ phenotypes, patients with ‘Double-Hit’ presented a dismal prognosis and significantly high TMB. Through chemotherapy sensitivity analysis, we identified a total of 30 sensitive drugs for ICC patients, of which 22 were drugs were sensitive to ‘Double-WT’, 7 drugs were sensitive to ‘Double-Hit’, and only one drug was sensitive to ‘Single-Hit’. Conclusion: Our study defined a novel mutation classification based on the common FMGs, which may contribute to the individualized treatment and management of ICC patients.